Testing the Seven-Factor Model of Academic Motivation (MUSIC) in Medical Sciences Students - Farzaneh Michaeli Manee; Elham Salehi; Rahim Baghaei; Mehran Alipour (مجله ایرانی آموزش در علوم پزشکی, 2017)
Introduction: Academic motivation can be perceived as a factor in deciding to continue academic education. One of the new models in this area is Jones’s model of academic motivation (MUSIC). This study aimed to test the seven-factor structure of this motivation model in medical sciences students.